2012
DOI: 10.1073/pnas.1203350109
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal growth in humans and postnatal brain maturation into late adolescence

Abstract: Prenatal life encompasses a critical phase of human brain development, but neurodevelopmental consequences of normative differences in prenatal growth among full-term pregnancies remain largely uncharted. Here, we combine the power of a withinmonozygotic twin study design with longitudinal neuroimaging methods that parse dissociable components of structural brain development between ages 3 and 30 y, to show that subtle variations of the in utero environment, as indexed by mild birth weight (BW) variation withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
187
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 53 publications
9
187
1
Order By: Relevance
“…We targeted early candidate factors that could potentially impact cortical area and general cognitive function, and hypothesized that such influences on brain and cognition in development would have continuous impacts. The targeted factors included pre-and neonatal biomedical health variables (26,27), specifically length of gestation (28), birth weight (26,27), and Apgar score obtained 5 min after birth (a measure of newborn vital signs) (29), as well as socioeconomic variables (30) [i.e., parental education, income, and single parenthood (31)]. An independent sample of twins was used to estimate the heritability of the surface area of the identified cortical regions, and how much of the phenotypic correlations of cortical area and GCA that could be accounted for by genetic factors.…”
mentioning
confidence: 99%
“…We targeted early candidate factors that could potentially impact cortical area and general cognitive function, and hypothesized that such influences on brain and cognition in development would have continuous impacts. The targeted factors included pre-and neonatal biomedical health variables (26,27), specifically length of gestation (28), birth weight (26,27), and Apgar score obtained 5 min after birth (a measure of newborn vital signs) (29), as well as socioeconomic variables (30) [i.e., parental education, income, and single parenthood (31)]. An independent sample of twins was used to estimate the heritability of the surface area of the identified cortical regions, and how much of the phenotypic correlations of cortical area and GCA that could be accounted for by genetic factors.…”
mentioning
confidence: 99%
“…Here the inside and outside surfaces of the cortex are segmented using deformable models and measures such as cortical thickness and surface area are extracted [12][13][14] . The diverse anatomical metrics that can be extracted from threedimensional models of the cortical surface capture different developmental processes, and show dissociable correlations with demographic 15,16 , genetic 17,18 , environmental 19 , and clinical 20,21 variables -highlighting the value in moving classical volumetric approaches to anatomical analysis. Surface based methods also provide an improved coordinate system for the cerebral cortex, allowing for smoothing of signal on the cortical sheet and surface based alignment to bring individuals into closer correspondence for statistical comparisons 13,22 .…”
Section: Macro-and Meso-scopic Neuroanatomymentioning
confidence: 99%
“…Box 3: developmental structural neuroimaging Our first major longitudinal insight into the dynamics of in vivo human brain development came from a structural neuroimaging study 157 , which revealed that the maturational trajectory of human gray matter volume follows a curvilinear "inverted-U", rather than showing a linear progression to adult values. Since this seminal study there has been a steep climb in the number of large-scale longitudinal structural neuroimaging datasets 158 and associated research reports detailing the spatiotemporal heterogeneity of neuroanatomical maturation within the brain 16,159 , and charting how the dynamics of structural brain development can vary as a function of genetic 160 , environmental 19 , demographic (e.g. biological sex 159 ), cognitive 161 and clinical 162 factors.…”
Section: Box 2: Population Neurosciencementioning
confidence: 99%
“…Intrigued by the converse speculation-that HDlh pairings denote disrupted asymmetry determination-we used in vivo structural neuroimaging data to explicitly test whether within-pair discordance for cerebral asymmetry is greater in HDlh than in HDll pairs. In one structural brain MRI scan for each member of the 17 HD MZ pairs in our sample, we derived measures of local surface area (SA) at ∼40,000 points (vertices) in each cerebral hemisphere as previously described (2). We then quantified pair-wise SA asymmetry concordance by correlating intervertex differences in SA asymmetry [(Left − Right)/(Left + Right) × 0.5] within each twin pair.…”
Section: (144)] With Hc Twins Intermediate [110 (115)]mentioning
confidence: 99%
“…We are grateful for Professor Segal's interesting letter (1), prompting us to delve deeper into a question that was nested within, but not directly addressed by our recent article (2): Are relationships between birth weight (BW) and intelligence quotient (IQ) variation within twin pairs modulated by patterns of handedness discordance? In a sample of 67 monozygotic (MZ) twin pairs (of which ∼40% pairs were discordant for handedness), Professor Segal had found that lower IQ most often segregated with lower BW in handedness-discordant twin pairs when the left-handed member had the lower BW (3).…”
mentioning
confidence: 99%